TRANSFORMASI BUDAYA NTT: REFLEKSI AKTOR SEBAGAI UPAYA MENGATASI KEMISKINAN DAN MENAIKKAN IPM (INDEKS PEMBANGUNAN MANUSIA) - Slamet Kusharyadi; Anil Dawan (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2022)
This article aims to describe the practice of cultural transformation in NTT in order to overcome poverty and increase HDI. Poverty and low HDI are caused by a cultural burden which is a high social cost and causes a financial burden for the community to increase their HDI. Critical analytical description which is the result of reflection of the process of cultural transformation of NTT as an effort to overcome poverty and increase the HDI Human Development Index in NTT. The method is descriptive, analytical and reflective of the process that has been undertaken by the author as a facilitator who is directly involved in transforming the culture of NTT. The results of this reflection find that the shackles of customary social costs and the shackles of customary relations patterns are the cause of poverty. Efforts to increase per capita income and the NTT Human Development Index require a cultural transformation. Cultural transformation has several key elements, namely: the process involves stakeholders, actors as middlemen and stakeholders involved and the challenges faced, results that can be replicated in other areas.